Making a little go a long way: A corpus-based analysis of a high-frequency word and some pedagogical implications for young Spanish learners - Labrador de la Cruz, Belén (International Journal of English Studies, 2019)
This study explores the different uses of the word little, its equivalents in Spanish and its teaching to young Spanish learners. First, it aims at analyzing the lexico-grammatical behavior of little in a corpus of children’s short stories, where its prevailing use, preceding countable nouns, has been found to be much more frequent than in other domains and registers. A contrastive study follows, which examines how little has been translated in an English-Spanish parallel corpus; the results show that diminutives constitute an important equivalent. Finally, some didactic implications are proposed, with the application of corpus-based findings to the teaching of English to young Spanish learners from an approach that combines lexical syllabi and story-based methodologies.